50 Management of atrial fibrillation in tachycardia-induced HF-REF: slow and steady wins the race. (16th October 2019) - Quinn, S; Farrell, C; McGlynn, K; David, S; Aleong, G
Abstract : Aims and objectives: Heart Failure (HF) and Atrial Fibrillation (AF) are concomitant in many patients. They share common risk factors and can exacerbate or precipitate each other. The aim of this study was to examine the management of patients presenting to Letterkenny University Hospital who were assessed to have tachycardia-induced cardiomyopathy. Methods: Patients known to the heart failure support service that had a diagnosis of tachycardia-induced cardiomyopathy were included in this review. Additionally, a HIPE search was undertaken for primary admissions for AF and secondary diagnosis of HF and the medical clinical file reviewed. Patients with known ischaemic heart disease or preserved ejection fraction HF were excluded. Data was analysed using SPSS. Results: 48 patients were identified, with a mean age of 67 yrs. The majority had AF and HF diagnosed on the same admission. Hypertension was the most common comorbidity. 96% of patients had an ejection fraction (EF) of <40% at presentation. The majority of patients were appropriately anti-coagulated and had appropriate levels of HF medications (ACE-I/Beta-blockers/MRA). 44% underwent direct current cardioversion with an additional 6% reverting to sinus rhythm chemically or spontaneously. While the total group showed increased EF at one year, those who remained in SR had markedly better improvements with only 12% remaining at EF < 40% compared to 46% of those who were in AF at follow up. Conclusion: Tachycardia induced cardiomyopathy is a potentially reversible cause of heart failure and when sinus rhythm is restored it resulted in substantial increases in EF. This group of patients should be identified for early rhythm control in order to improve outcomes.